Nε-Lysine Acetylation of the Histone-Like Protein HBsu Regulates the Process of Sporulation and Affects the Resistance Properties of Bacillus subtilis Spores - Luu, Jackson; Mott, Connor M.; Schreiber, Olivia R.; Giovinco, Holly M.; Betchen, Melanie; Carabetta, Valerie J. (Frontiers in Microbiology, 2022)
Bacillus subtilis produces dormant, highly resistant endospores in response to extreme environmental stresses or starvation. These spores are capable of persisting in harsh environments for many years, even decades, without essential nutrients. Part of the reason that these spores can survive such extreme conditions is because their chromosomal DNA is well protected from environmental insults. The α/β-type small acid-soluble proteins (SASPs) coat the spore chromosome, which leads to condensation and protection from such insults. The histone-like protein HBsu has been implicated in the packaging of the spore chromosome and is believed to be important in modulating SASP-mediated alterations to the DNA, including supercoiling and stiffness. Previously, we demonstrated that HBsu is acetylated at seven lysine residues, and one physiological function of acetylation is to regulate chromosomal compaction. Here, we investigate if the process of sporulation or the resistance properties of mature spores are influenced by the acetylation state of HBsu. Using our collection of point mutations that mimic the acetylated and unacetylated forms of HBsu, we first determined if acetylation affects the process of sporulation, by determining the overall sporulation frequencies. We found that specific mutations led to decreases in sporulation frequency, suggesting that acetylation of HBsu at some sites, but not all, is required to regulate the process of sporulation. Next, we determined if the spores produced from the mutant strains were more susceptible to heat, ultraviolet (UV) radiation and formaldehyde exposure. We again found that altering acetylation at specific sites led to less resistance to these stresses, suggesting that proper HBsu acetylation is important for chromosomal packaging and protection in the mature spore. Interestingly, the specific acetylation patterns were different for the sporulation process and resistance properties of spores, which is consistent with the notion that a histone-like code exists in bacteria. We propose that specific acetylation patterns of HBsu are required to ensure proper chromosomal arrangement, packaging and protection during the process of sporulation.